Sovereign Necropolis : The Politics of Death in Semi-Colonial Siam - Pearson, Trais, 1979- (Book collections on Project MUSE., 2020)
"This book recovers a hidden tradition of Thai political life in the era of high imperialism by examining legal and medico-legal interventions in death"--